The Effect of Auditor's Emotional Intelligence, Competence, and Independence on Audit Quality - Sherly Pinatik (International Journal of Applied Business and International Management, 2021)
The duty of auditor is examining and providing an opinion on the fairness of the financial statements of a business entity based on determining standards. Based on the foregoing, the auditor must maintain audit quality. This study aims to analyze the effect of emotional intelligence, competence, and auditor independence on audit quality. This study used a survey method with a quantitative descriptive approach. The sample in this study were all auditors of BPK RI representatives of North Sulawesi Province, as many as 61 respondents. Data analysis techniques were collected through the distribution of questionnaires which were rated and tabulated for analysis and the answers obtained by respondents were by predetermined variable values and being analyzed by using the Amos 24 software, where the data analysis technique was carried out to determine the effect of the SEM analysis approach. The results showed that the emotional intelligence variable had a positive and significant effect on audit quality, competence had a positive and significant effect on audit quality, and independence had a positive and significant effect on audit quality. It is hoped that these research results can be used as material or measurement indicators for BPK institutional auditors to recruit auditors based on knowledge and morals, and character.